The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.3928/1081597x-20160513-01
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Keratoconus in a Tertiary Referral Center: Incidence, Presentation, Risk Factors, and Treatment

Abstract: The incidence of pediatric keratoconus indicates that increased awareness for keratoconus among children is needed, mainly in cases of family history of keratoconus, ocular allergy/pruritus, poor CDVA, corneal hydrops, and/or high astigmatism. [J Refract Surg. 2016;32(8):534-541.].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
45
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(53 citation statements)
references
References 34 publications
4
45
0
4
Order By: Relevance
“…Visual rehabilitation in early and moderate stages consists of spectacles, contact lenses, and intracorneal ring implantation …”
Section: Resultsmentioning
confidence: 99%
“…Visual rehabilitation in early and moderate stages consists of spectacles, contact lenses, and intracorneal ring implantation …”
Section: Resultsmentioning
confidence: 99%
“…In Lebanon, El-Khoury et al reported an incidence of 0.53% in children 14 years or younger who were diagnosed in a tertiary referral eye center. 2 Another study conducted in southwestern Nigeria reported 0.08% prevalence of blindness among school children due to KC. 3 A recent study was conducted in Saudi Arabia reported 4.79% prevalence among the pediatric age group.…”
Section: Introductionmentioning
confidence: 98%
“…Keratoconus is a degenerative corneal disease which more observed in men [3,5,7,8]. This situation is based on our patient population's majority is men.…”
Section: Discussionmentioning
confidence: 99%
“…Retinal reflection scattering is the earliest findings of keratoconus and corneal reflection on the nasal cornea when a penlight is shone from the temporal side as Rizutti's sign is other early findings [4]. Ocular allergy and itching are play a role in keratoconus etiology [5]. The prevalence of keratoconus in the middle-eastern countries is much higher than in the regions of the world.…”
Section: Introductionmentioning
confidence: 99%